How Formerly Incarcerated Women Confront the Limits of Caring and the Burdens of Control Amid California's Carceral Realignment. (January 2019) - Welsh, Megan
The largest scale effort to reduce our reliance on incarceration is currently taking place in California. Drawing on in-depth interviews with formerly incarcerated women on two different forms of community supervision in one California county, this article makes two main contributions. First, I offer a conceptual framework for understanding how women experience the goals of community supervision. Because actual rehabilitation is often off-limits, I suggest that these institutional goals are organized around caring, control, and self-governance: Caring is exhibited by supervision officers in lieu of substantive assistance toward rehabilitation; control for the sake of public safety remains a key aim of community supervision; and self-governance is an unstated institutional goal through which women are forced to take on the invisible work of managing their own rehabilitation. Second, I assess how—if at all—California's decarceration effort has shifted institutional goals, and what this means for women. I argue that decarceration's continued emphasis on control for the sake of public safety impedes the transformative potential of efforts to restructure the crime-processing system.